2018
DOI: 10.3390/su11010118
|View full text |Cite
|
Sign up to set email alerts
|

Developing Evaluation Frameworks for Business Models in China’s Rural Markets

Abstract: In rural China, successful and sustainable business model design has been viewed as an important strategy to achieve a win–win scenario in which rural poverty can be alleviated and enterprise profit can be improved. Although business model related literature is strong, it lacks a comprehensive framework for appraising business models in rural markets. As a result, entrepreneurs are facing significant challenges in implementing their market development centered business models or resource development centered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…The highest bidder, typically a semi-urban wholesaler (middlemen), buys the entire item. This identification from field interviews is consistent with the findings from the literature review (Lu and Yang, 2004; Paulraj et al , 2006; Jensen, 2007; Matani, 2007; Weerakkody et al , 2007; Schipmann and Qaim, 2011; Trienekens, 2011; Bao et al , 2012; Bosona and Gebresenbet, 2013; Somashekhar et al , 2014; Bloom, 2015; Silvestre, 2015; Emana et al , 2017; Dubey et al , 2018b; Zhang et al , 2019) on the supply chain of agricultural food items, flowers and fishes in many developing countries such as China, Taiwan, India, Bangladesh, Indonesia, Sri Lanka, Brazil, Mexico, South Africa, Uganda, Tanzania, Ethiopia, Kenya, etc.…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…The highest bidder, typically a semi-urban wholesaler (middlemen), buys the entire item. This identification from field interviews is consistent with the findings from the literature review (Lu and Yang, 2004; Paulraj et al , 2006; Jensen, 2007; Matani, 2007; Weerakkody et al , 2007; Schipmann and Qaim, 2011; Trienekens, 2011; Bao et al , 2012; Bosona and Gebresenbet, 2013; Somashekhar et al , 2014; Bloom, 2015; Silvestre, 2015; Emana et al , 2017; Dubey et al , 2018b; Zhang et al , 2019) on the supply chain of agricultural food items, flowers and fishes in many developing countries such as China, Taiwan, India, Bangladesh, Indonesia, Sri Lanka, Brazil, Mexico, South Africa, Uganda, Tanzania, Ethiopia, Kenya, etc.…”
Section: Methodssupporting
confidence: 87%
“…To recognize the problems and develop an efficient supply chain reflecting the identified problems, this research has also explored literature on resilient supply chains and issues related to fragile structural dynamics of the supply chain of perishable products. Several researchers dealing with rural food items or perishable items procured from remote and fragmented locations revealed that these markets are at the bottom of the pyramid (Surana et al , 2005; Singh, 2011; Fawcett et al , 2012; Mena et al , 2013; Zhang et al , 2019). This scenario reflects a very scattered and unorganized connection among the stakeholders who apparently should create a network of supply structure (Zhang et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors led to the lack of success of these programs, one of the most dominant factors being too much government intervention. Consequently, it inhibited the creativity and innovation of rural communities in managing and running the economic machinery in rural areas (Ho et al, 2019, Lyon-Hillet al, 2019, Tang, 2019, Wei & Li, 2019and Zhang et al, 2019. The system and the mechanism of economic institutions in rural areas do not work effectively and have an inclination for dependence on government assistance so that it turns off the spirit of independence.…”
Section: Introductionmentioning
confidence: 99%